Magnetic enhanced denitration catalyst as well as preparation method and application thereof
By using magnetically strengthened denitrification catalysts with components such as CeO2, sodium citrate, TiO2@Fe3O4 and MnFe2O4, the problem of degradation of existing catalysts in high temperature and high sulfur environments is solved, and efficient and stable NOx reduction and sulfur resistance are achieved. Poisoning ability extends the service life of the catalyst.
Patent Information
- Application Number
- CN202411505619.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The performance of existing denitrification catalysts decreases in high temperature and high sulfur environments, and the active components are easily lost, resulting in a shortening of the catalyst life and efficiency.
Using CeO2 as the main active component, sodium citrate as the morphological regulator, TiO2@Fe3O4 as the carrier, MnFe2O4 as the anchor and co-active component, magnetically strengthened denitrification catalyst is prepared by multiple hydrothermal and strong acid-regulating hydrothermal methods. Achieve efficient assembly of active components and carriers.
Highly efficiently catalyzed NOx reduction at medium and low temperatures, it has excellent anti-sulfur poisoning ability and anti-active component loss ability, extending the service life of the catalyst and improving its stability.
Smart Images

Figure CN119386888A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic enhanced denitration catalyst and a preparation method thereof, and belongs to the field of industrial flue gas purification. Background Art
[0002] With the advancement of industrialization, NO x As a major flue gas pollutant, emissions have increased dramatically. x It can easily cause acid rain and react with volatile organic compounds to produce photochemical smog, which harms the respiratory system of organisms. x It is a precursor to ground-level ozone, which has a negative impact on human health and the ecosystem. Therefore, many countries and regions have formulated strict air quality standards to reduce nitrogen oxide emissions. In particular, with the increase in production demand, industrial activities have become NO x In order to reduce the impact of these harmful gases on the environment and human health, it is necessary to use a denitrification catalyst to promote NO x It reacts with the reducing agent and converts it into harmless nitrogen and water, thus significantly reducing pollutant emissions. This technology has the advantages of high efficiency, stability and economy, making it a popular choice for controlling NO x The core technology of this method is the design and development of denitrification catalysts. At the same time, with increasingly stringent emission requirements, the existing denitrification catalysts need to be further improved and upgraded. Therefore, the development of more efficient and stable denitrification catalysts is an important technical development direction to solve the existing emission policies and actual production emission problems.
[0003] Among the existing denitration catalyst patents, patent CN201810289079.2 uses a method for preparing an alkali metal poisoned low-temperature manganese-based SCR denitration catalyst to prepare a catalyst that has high efficiency in catalytic reduction of NO in an application environment with low temperature and a certain amount of potassium salt or sodium salt as the main characteristics. x The patent CN202211341584.X discloses a low-temperature manganese-based SCR denitrification catalyst resistant to alkali metal poisoning. The catalyst prepared by the method of preparing a low-temperature manganese-based SCR denitrification catalyst resistant to alkali metal poisoning has high catalytic reduction of NO in an application environment with low temperature and a certain amount of potassium salt or sodium salt as the main characteristics. xperformance, so as to adapt to high alkali metal content fuel, extend the catalyst life and improve the safety of use. Patent CN202211341584.X discloses a high-efficiency denitration catalyst, which is a denitration catalyst composited with CoO quantum dots and gC3N4 nanosheets. The gC3N4 nanosheets have a two-dimensional porous layered morphology, and the CoO quantum dots are evenly distributed on the surface of the g-C3N4 nanosheets. At present, conventional catalyst preparation methods are difficult to achieve efficient loading of catalyst carriers and active components. Therefore, the current preparation and research and development of catalysts needs to further promote the efficient combination of catalyst carriers and active components.
[0004] Therefore, the design of denitrification catalysts should first adopt reasonable means to construct catalysts with special morphology and solve the loading problem of activated components, so as to achieve efficient and stable removal efficiency under complex flue gas conditions. At the same time, the cost of this method should also be controlled within a reasonable range. Summary of the invention
[0005] The purpose of the present invention is to propose a magnetically enhanced denitrification catalyst in view of the current research status and existing problems of existing industrial flue gas denitrification catalysts. Another purpose of the present invention is to provide a method for preparing the above catalyst.
[0006] A magnetic enhanced denitrification catalyst and a preparation method thereof, with CeO2 as the main active component, sodium citrate as a morphology regulator, TiO2@Fe3O4 as a carrier, MnFe2O4 as an anchoring agent and an auxiliary active component, and multiple hydrothermal and strong acid controlled hydrothermal methods to achieve the preparation of TiO2@Fe3O4 nanosphere carriers, the synthesis of CeO2-MnFe2O4 active components, and the efficient assembly of active components and nanosphere carriers. Among them, based on the mass of the carrier, the mass percentage of the active component is 5-25%.
[0007] In the above catalyst: the mass ratio of TiO2:Fe3O4 in the carrier is (1~10):1; the mass ratio of CeO2:MnFe2O4 in the active component is (1-10):1; based on the mass of the carrier, the mass percentage of the active component is 1~15%.
[0008] In the above catalyst: the mass ratio of TiO2:Fe3O4 in the carrier is (5-10):1; the mass ratio of CeO2:MnFe2O4 in the active component is (2-5):1; based on the mass of the carrier, the mass percentage of the active component is 8-15%.
[0009] A method for preparing the above-mentioned magnetic enhanced denitration catalyst, the preparation method of the catalyst is as follows:
[0010] (1) Preparation of nano-Fe3O4 materials
[0011] The iron salt is added into deionized water and stirred evenly, and then transferred into a hydrothermal reactor for the first hydrothermal reaction, and then filtered and dried to obtain nano-Fe3O4;
[0012] (2) Preparation of TiO2@Fe3O4 nanosphere carrier
[0013] Weigh the nano-Fe3O4 prepared in step (2), the titanium source and sodium citrate, add them into deionized water and stir evenly, transfer them to a hydrothermal reactor for a second hydrothermal treatment and then filter, and transfer the filtered solid matter to a muffle furnace for calcination to obtain a TiO2@Fe3O4 nanosphere carrier;
[0014] (3) Synthesis of CeO2-MnFe2O4 active components
[0015] Weigh cerium salt, manganese salt, iron salt and sodium hydroxide, add them into deionized water and stir evenly, transfer them into a hydrothermal reactor, hydrothermally heat for the third time, filter and dry to obtain CeO2-MnFe2O4 active component;
[0016] (4) Catalyst molding preparation
[0017] The TiO2@Fe3O4 nanosphere carrier prepared in step (2), the CeO2-MnFe2O4 active component obtained in step (3), and concentrated sulfuric acid are weighed, added to deionized water, and stirred evenly. The mixture is transferred to a hydrothermal reactor for the fourth hydrothermal treatment, and then filtered and dried to obtain a molded catalyst.
[0018] In the above preparation method: the iron salt described in step (1) is a combination of ferrous sulfate heptahydrate and ferric chloride hexahydrate, the mass ratio of ferrous sulfate heptahydrate: ferric chloride hexahydrate is 1: (1-5), the temperature of the first hydrothermal reaction is 100-120° C., and the time is 2-3 hours.
[0019] In the above preparation method: the titanium source described in step (2) is tetrabutyl titanate, and the mass ratio of nano-Fe3O4: tetrabutyl titanate: sodium citrate is (1-5): (10-45): (0.01-1);
[0020] The temperature of the second hydrothermal reaction in step (2) is 120-180° C., and the time is 1-2 hours; the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.
[0021] In the above preparation method: the cerium salt described in step (3) is cerium nitrate hexahydrate, the manganese salt is manganese nitrate tetrahydrate, the iron salt is ferric chloride hexahydrate, and the mass ratio of cerium nitrate hexahydrate: manganese nitrate tetrahydrate: ferric chloride hexahydrate: sodium hydroxide is (5-16): (1-3): (2-4): (4-12);
[0022] The temperature of the third hydrothermal reaction in step (3) is 120-180° C. and the time is 2-6 hours.
[0023] In the above preparation method: the mass ratio of the TiO2@Fe3O4 nanosphere carrier: CeO2-MnFe2O4: concentrated sulfuric acid: deionized water described in step (4) is (10-20): (1-5): (0.01-1): (50-90).
[0024] In the above preparation method: the fourth hydrothermal temperature in step (4) is 120-150° C., and the hydrothermal time is 4-6 hours.
[0025] In the technical solution of the present invention, the catalyst is used in the purification of nitrogen oxides in industrial flue gas.
[0026] The catalyst activity test conditions of the present invention are as follows:
[0027] Measure 1.0mL of 20-40 mesh catalyst and pour it into a quartz tube with an inner diameter of 8mm. Fix both ends of the catalyst with quartz wool and place it in a programmed temperature tube furnace. The gas distribution system simulates the flue gas components: NO (500ppm), NH3 (500ppm), SO2 (100ppm), O2 (11vol.%), N2 is the carrier gas, and the total gas flow rate is 500mL / min. The catalyst temperature test range is 200-400℃, and each 50℃ is a test temperature point. After each temperature test point is kept warm for 25 minutes, the activity test is carried out.
[0028] Beneficial effects of the present invention:
[0029] The catalyst prepared by the present invention can catalytically reduce NO with high efficiency at medium and low temperatures, and the catalyst has excellent resistance to sulfur poisoning and loss of active components. The specific basis is as follows:
[0030] (1) Ferrous salts with different valence states of iron elements are subjected to a hydrothermal reaction to generate nano-Fe3O4. Nano-scale Fe3O4 has a small particle size and a large specific surface area, and as an excellent "core" carrier, it provides favorable conditions for the subsequent loading of TiO2. Sodium citrate is used as a morphology regulator to convert the titanium source into TiO2 under high-temperature hydrothermal conditions and coat the surface of Fe3O4 to form a nano-spherical composite carrier. Fe3O4 is in the inner layer and plays a supporting role, while making the interior of the TiO2@Fe3O4 nano-spherical carrier have magnetic absorption properties. The filtered TiO2@Fe3O4 nano-spherical carrier is further subjected to high-temperature calcination. On the one hand, high-temperature calcination promotes the formation of anatase TiO2. This crystal type of TiO2 has a stable structure and has the largest specific surface area compared to other representative crystal types of TiO2, which helps to increase the strength of the active component binding to it. On the other hand, high-temperature calcination can promote the thermal decomposition of residual sodium citrate on the surface of the carrier. During the thermal decomposition, the gas generated is separated from the surface of the carrier, resulting in more pore structures.
[0031] (2) Cerium (Ce) has a unique 4f electron layer structure, and when used in combination with elements such as Mn and Fe, it can exhibit unique synergistic catalytic properties. The spinel ferrite MnFe2O4 has a high catalytic efficiency, but its own magnetism causes the catalyst particles to easily agglomerate. The combination of CeO2 and MnFe2O4 as an active component can not only exert the synergistic catalytic properties of CeO2, but also CeO2 can reduce the degree of agglomeration of MnFe2O4, thereby avoiding the disadvantages brought about by the magnetic properties of MnFe2O4.
[0032] (3) The catalyst is hydrothermally formed in a strong acid-controlled manner. The introduction of sulfuric acid will generate sulfate ions by replacing oxygen atoms on the surface of the TiO2@Fe3O4 carrier. The enhanced acidity of the catalyst carrier surface enhances the catalyst's adsorption effect on the reducing agent NH3, while weakening the adsorption capacity of sulfuric acid-containing gases such as SO3 on the catalyst surface, thereby improving the catalyst's resistance to sulfur poisoning at the physical adsorption level. From the perspective of chemical reactions, transition metal oxides represented by Mn and Fe are prone to react with SO2 in industrial flue gas to generate sulfates, which leads to a serious decline in catalyst performance. This method significantly reduces the catalyst's SO2→SO3 conversion rate by pre-generating sulfate ions, that is, the sulfate content is significantly reduced. The above two aspects ensure the excellent resistance to sulfur poisoning of this catalyst.
[0033] (4) Industrial flue gas often contains dust, and the scouring of dust causes the loss of active components of the catalyst prepared by the prior art, which seriously shortens the service life and catalytic activity of the catalyst. This method generates a magnetic active component by combining the main active component with the magnetic spinel ferrite MnFe2O4. In addition, the interior of the TiO2@Fe3O4 nanosphere carrier has magnetic attraction properties, which further strengthens the combination of the active components of the catalyst and the carrier through magnetic attraction. Under dusty conditions, the active components of the catalyst have a high bonding strength with the carrier and are not easy to lose. The nanosphere carrier can also ensure that the overall structure of the catalyst does not collapse under the action of internal magnetic support. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope image of the catalyst prepared in Example 2.
[0035] Figure 2 This is a scanning electron microscope image of the catalyst prepared in Comparative Example 2.
[0036] Figure 3 The performance diagram of NO removal of the catalysts prepared in Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0038] The catalyst activity test conditions of the present invention are as follows:
[0039] Measure 1.0mL of 20-40 mesh catalyst and pour it into a quartz tube with an inner diameter of 8mm. Fix both ends of the catalyst with quartz wool and place it in a programmed temperature tube furnace. The gas distribution system simulates the flue gas components: NO (500ppm), NH3 (500ppm), SO2 (100ppm), O2 (11vol.%), N2 is the carrier gas, and the total gas flow rate is 500mL / min. The catalyst temperature test range is 200-400℃, and each 50℃ is a test temperature point. After each temperature test point is kept warm for 25 minutes, the activity test is carried out.
[0040] Example 1
[0041] (1) Preparation of nano-Fe3O4 materials
[0042] Weigh 2.5000g of ferrous sulfate heptahydrate and 5.0000g of ferric chloride hexahydrate, add them into 75.0000g of deionized water and stir evenly, transfer to a hydrothermal reactor, hydrothermal at 100℃ for 2h, filter and dry to obtain nano-Fe3O4;
[0043] (2) Preparation of TiO2@Fe3O4 nanosphere carrier
[0044] 1.0000g of the nano-Fe3O4 prepared in step (2), 21.3057g of tetrabutyl titanate, and 0.0600g of sodium citrate were weighed and added to 88.0000g of deionized water and stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal treatment at 180°C for 1h and filtered. The filtered solid matter was transferred to a muffle furnace for calcination at 500°C for 2h to obtain a TiO2@Fe3O4 nanosphere carrier. The mass ratio of TiO2:Fe3O4 in the carrier was 5:1.
[0045] (3) Synthesis of CeO2-MnFe2O4 active components
[0046] 5.0457g of cerium nitrate hexahydrate, 1.0884g of manganese nitrate tetrahydrate, 2.3440g of ferric chloride hexahydrate and 4.0000g of sodium hydroxide were weighed and added to 50.0000g of deionized water and stirred evenly, transferred to a hydrothermal reactor and hydrothermally heated at 150°C for 2h, and then filtered and dried to obtain CeO2-MnFe2O4 active components. Among them, the mass ratio of CeO2:MnFe2O4 in the active component is 2:1.
[0047] (4) Catalyst molding preparation
[0048] Based on the mass of the carrier, the mass percentage of the active component is 8%. Weigh 14.0000g of the TiO2@Fe3O4 nanosphere carrier obtained in step (2), 1.1200g of the CeO2-MnFe2O4 active component obtained in step (3), and 0.0700g of concentrated sulfuric acid, add them to 56.0000g of deionized water, stir evenly, transfer to a hydrothermal reactor, hydroheat at 120°C for 4h, filter and dry to obtain a molded catalyst;
[0049] Example 2
[0050] (1) Preparation of nano-Fe3O4 materials
[0051] Weigh 2.0000g of ferrous sulfate heptahydrate and 6.0000g of ferric chloride hexahydrate, add them into 100.0000g of deionized water and stir evenly, transfer to a hydrothermal reactor and heat at 120℃ for 3h, then filter and dry to obtain nano-Fe3O4;
[0052] (2) Preparation of TiO2@Fe3O4 nanosphere carrier
[0053] 1.0000g of the nano-Fe3O4 prepared in step (2), 42.6114g of tetrabutyl titanate, and 0.4000g of sodium citrate were weighed and added to 80.0000g of deionized water and stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal treatment at 180°C for 1h and filtered. The filtered solid matter was transferred to a muffle furnace for calcination at 600°C for 4h to obtain a TiO2@Fe3O4 nanosphere carrier. The mass ratio of TiO2:Fe3O4 in the carrier was 10:1.
[0054] (3) Synthesis of CeO2-MnFe2O4 active components
[0055] 15.1371g of cerium nitrate hexahydrate, 1.3061g of manganese nitrate tetrahydrate, 2.8128g of ferric chloride hexahydrate and 12.0000g of sodium hydroxide were weighed and added to 100.0000g of deionized water and stirred evenly, transferred to a hydrothermal reactor and hydrothermally heated at 180°C for 4h, and then filtered and dried to obtain CeO2-MnFe2O4 active component. Among them, the mass ratio of CeO2:MnFe2O4 in the active component is 5:1.
[0056] (4) Catalyst molding preparation
[0057] Based on the mass of the carrier, the mass percentage of the active component is 15%. 16.0000g of the TiO2@Fe3O4 nanosphere carrier obtained in step (2), 2.4000g of the CeO2-MnFe2O4 active component obtained in step (3), and 0.1600g of concentrated sulfuric acid are added to 80.0000g of deionized water and stirred evenly, transferred to a hydrothermal reactor, hydrothermally heated at 150°C for 6h, and then filtered and dried to obtain a molded catalyst.
[0058] Example 3
[0059] (1) Preparation of nano-Fe3O4 materials
[0060] Weigh 3.0000g of ferrous sulfate heptahydrate and 7.5000g of ferric chloride hexahydrate, add them into 120.0000g of deionized water and stir evenly, transfer to a hydrothermal reactor and heat at 110℃ for 3h, then filter and dry to obtain nano-Fe3O4;
[0061] (2) Preparation of TiO2@Fe3O4 nanosphere carrier
[0062] 1.0000g of the nano-Fe3O4 prepared in step (2), 31.9585g of tetrabutyl titanate, and 0.2800g of sodium citrate were weighed and added to 63.0000g of deionized water and stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal treatment at 180°C for 1h and filtered. The filtered solid matter was transferred to a muffle furnace for calcination at 600°C for 2h to obtain a TiO2@Fe3O4 nanosphere carrier. The mass ratio of TiO2:Fe3O4 in the carrier was 5:1.
[0063] (3) Synthesis of CeO2-MnFe2O4 active components
[0064] 7.0640g of cerium nitrate hexahydrate, 1.5237g of manganese nitrate tetrahydrate, 3.2816g of ferric chloride hexahydrate and 8.0000g of sodium hydroxide were weighed and added to 75.0000g of deionized water and stirred evenly, transferred to a hydrothermal reactor and hydrothermalized at 180°C for 2h, and then filtered and dried to obtain CeO2-MnFe2O4 active component. Among them, the mass ratio of CeO2:MnFe2O4 in the active component is 2:1.
[0065] (4) Catalyst molding preparation
[0066] Based on the mass of the carrier, the mass percentage of the active component is 10%. Weigh 16.0000g of the TiO2@Fe3O4 nanosphere carrier obtained in step (2), 1.6000g of the CeO2-MnFe2O4 active component obtained in step (3), and 0.1200g of concentrated sulfuric acid, add them to 72.0000g of deionized water, stir evenly, transfer to a hydrothermal reactor, hydroheat at 150°C for 6h, and then filter and dry to obtain a molded catalyst.
[0067] Comparative Example 1
[0068] 1. Synthesis of CeO2-MnFe2O4 active components
[0069] During the synthesis of the CeO2-MnFe2O4 active component, cerium nitrate hexahydrate was not added, and the rest was the same as in Example 1.
[0070] 2. Activity Test Results
[0071] like Figure 3 As shown, due to the lack of addition of the main active component cerium oxide, MnFe2O4 is severely agglomerated, the specific surface area decreases, and the excellent redox performance brought by cerium oxide is lost, resulting in a decrease in catalytic performance. The test results show that the NO removal efficiency is only 34.3% at 200°C.
[0072] Comparative Example 2
[0073] 1. Preparation of TiO2@Fe3O4 nanosphere carrier
[0074] The morphology control agent sodium citrate was not added during the preparation of the TiO2@Fe3O4 nanosphere carrier, and the rest was the same as in Example 2.
[0075] 2. Activity Test Results
[0076] like Figure 2 As shown, due to the lack of addition of morphology regulator sodium citrate, the final catalyst presents irregular particles and severe agglomeration, a decrease in specific surface area, and a small number of internal micropores, resulting in a decrease in catalytic performance. Test results show that the NO removal efficiency is 50.3% at 200°C.
[0077] Comparative Example 3
[0078] 1. Catalyst molding preparation
[0079] During the catalyst molding preparation, concentrated sulfuric acid was not added for acid regulation, and the rest was the same as in Example 3.
[0080] 2. Activity Test Results
[0081] like Figure 3 As shown, due to the lack of concentrated sulfuric acid for acid regulation, the catalyst's resistance to sulfur poisoning decreased. The test results showed that the NO removal efficiency was 59.6% at 400°C.
Claims
1. A magnetic enhanced denitration catalyst, characterized in that: The catalyst uses CeO2 as the main active component, sodium citrate as a morphology regulator, TiO2@Fe3O4 as a carrier, and MnFe2O4 as an anchoring agent and auxiliary active component. The preparation of TiO2@Fe3O4 nanosphere carrier, synthesis of CeO2-MnFe2O4 active component, and efficient assembly of active component and nanosphere carrier are achieved through multiple hydrothermal and strong acid-regulated hydrothermal methods. Among them, the mass percentage of the active component is 5-25% based on the mass of the carrier.
2. The magnetic enhanced denitration catalyst according to claim 1, characterized in that: The mass ratio of TiO2:Fe3O4 in the carrier is (1-10):1; the mass ratio of CeO2:MnFe2O4 in the active component is (1-10):1; based on the mass of the carrier, the mass percentage of the active component is 1-15%.
3. The magnetic enhanced denitration catalyst according to claim 2, characterized in that: The mass ratio of TiO2:Fe3O4 in the carrier is (5-10):1; the mass ratio of CeO2:MnFe2O4 in the active component is (2-5):1; based on the mass of the carrier, the mass percentage of the active component is 8-15%.
4. A method for preparing a magnetically enhanced denitration catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of nano-Fe3O4 materials The iron salt is added into deionized water and stirred evenly, and then transferred into a hydrothermal reactor for the first hydrothermal reaction, and then filtered and dried to obtain nano-Fe3O4; (2) Preparation of TiO2@Fe3O4 nanosphere carrier Weigh the nano-Fe3O4 prepared in step (2), the titanium source and sodium citrate, add them into deionized water and stir evenly, transfer them to a hydrothermal reactor for a second hydrothermal treatment and then filter, and transfer the filtered solid matter to a muffle furnace for calcination to obtain a TiO2@Fe3O4 nanosphere carrier; (3) Synthesis of CeO2-MnFe2O4 active components Weigh cerium salt, manganese salt, iron salt and sodium hydroxide, add them into deionized water and stir evenly, transfer them into a hydrothermal reactor, hydrothermally heat for the third time, filter and dry to obtain CeO2-MnFe2O4 active component; (4) Catalyst molding preparation The TiO2@Fe3O4 nanosphere carrier prepared in step (2), the CeO2-MnFe2O4 active component obtained in step (3), and concentrated sulfuric acid are weighed, added to deionized water, and stirred evenly. The mixture is transferred to a hydrothermal reactor for the fourth hydrothermal treatment, and then filtered and dried to obtain a molded catalyst.
5. The preparation method according to claim 4, characterized in that: The iron salt described in step (1) is a combination of ferrous sulfate heptahydrate and ferric chloride hexahydrate, the mass ratio of ferrous sulfate heptahydrate to ferric chloride hexahydrate is 1:(1-5), the temperature of the first hydrothermal reaction is 100-120° C., and the time is 2-3 hours.
6. The preparation method according to claim 4, characterized in that: The titanium source described in step (2) is tetrabutyl titanate, and the mass ratio of nano-Fe3O4: tetrabutyl titanate: sodium citrate is (1-5): (10-45): (0.01-1); The temperature of the second hydrothermal reaction in step (2) is 120-180° C., and the time is 1-2 hours; the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.
7. The preparation method according to claim 4, characterized in that: The cerium salt described in step (3) is cerium nitrate hexahydrate, the manganese salt is manganese nitrate tetrahydrate, and the iron salt is ferric chloride hexahydrate, and the mass ratio of cerium nitrate hexahydrate: manganese nitrate tetrahydrate: ferric chloride hexahydrate: sodium hydroxide is (5-16): (1-3): (2-4): (4-12); The temperature of the third hydrothermal reaction in step (3) is 120-180° C. and the time is 2-6 hours.
8. The preparation method according to claim 4, characterized in that: The mass ratio of the TiO2@Fe3O4 nanosphere carrier: CeO2-MnFe2O4: concentrated sulfuric acid: deionized water described in step (4) is (10-20): (1-5): (0.01-1): (50-90).
9. The preparation method according to claim 4, characterized in that: The fourth hydrothermal temperature in step (4) is 120-150° C., and the hydrothermal time is 4-6 hours.
10. Use of the catalyst according to claim 1 in purifying nitrogen oxides in industrial flue gas.
Citation Information
Patent Citations
Method for recovering waste SCR denitration catalyst and regenerated SCR denitration catalyst carrier powder
CN108525709A
Efficient denitration catalyst and preparation method thereof
CN115463683A